The Influence of Fluorian Atmospheric Waste on The Chemical Composition of Fruit and Vegetable Plants Grown in The Northern Districts of Surkhandarya Province - Ilhom Mamarajabovich Samadov; Mamanazarova Maksuda Orazalieva; Alieva Dildora Fakhriddinovna; Shopo'latova Xonzodabanu Baxtiyor qizi (Scientific Trends, 2022)
In this article, the effect of fluorine compounds released into the environment from the State Unitary Enterprise of Tajikistan Aluminum Company (TALKO DUK) on the amount of macro and microelements in agricultural crops and the activity of the peroxidase enzyme in plant leaves is presented in this article.
Keywords: fluorine, macro and microelements, atrophic environment, aluminum, steel